Peran External Relation PT KCI Dalam Upaya Meningkatkan Corporate Image - Alfian Nur Firdaus; Iin Soraya; Sari Ekowati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The role of PT KCI's External Relations in efforts to improve its Corporate Image is important to provide a positive view of the public. This cannot be separated from how External Public Relations carries out its role with a managerial concept. This research aims to analyze the role of PT KCI's external public relations. This research uses the concept of Managerial roles. This research method uses qualitative methods, the data collection techniques used are interviews, observation and documentation. The results of this research found the role of External Relations in improving corporate image with expert communication experts, problem-solving process facilitators, communication facilitators and communication technicians. And the obstacles include internal and external obstacles, including operational problems, crisis communication, public and media perceptions, technological challenges, internal challenges, changes in government policy and social issues. The results of this analysis provide insight into the dynamics of the role of PT KCI's external public relations in efforts to improve its corporate image.